Persistence and cycles in US hours worked - Guglielmo Maria Caporale; Luis A. Gil-Alana (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper analyses monthly hours worked in the US over the sample period 1939m1 - 2011m10 using a cyclical long memory model; this is based on Gegenbauer processes and characterised by autocorrelations decaying to zero cyclically and at a hyperbolic rate along with a spectral density that is unbounded at a non-zero frequency. The reason for choosing this specification is that the periodogram of the hours worked series has a peak at a frequency away from zero. The empirical results confirm that this model works extremely well for hours worked, and it is then employed to analyse their relationship with technology shocks. It is found that hours worked increase on impact in response to a technology shock (though the effect dies away rapidly), consistently with Real Business Cycle (RBC) models.
Keywords: C32; E24; 330; hours worked; fractional integration; cycles; technology shocks; Arbeitszeit; Konjunktur; Technischer Fortschritt; Schock; Real Business Cycle; USA